GARP transcription factors repress Arabidopsis nitrogen starvation response via ROS-dependent and -independent pathways. (24th March 2021) - Safi, Alaeddine; Medici, Anna; Szponarski, Wojciech; Martin, Florence; Clément-Vidal, Anne; Marshall-Colon, Amy; Ruffel, Sandrine; Gaymard, Frédéric; Rouached, Hatem; Leclercq, Julie; Coruzzi, Gloria; Lacombe, Benoît; et al.
Abstract : A nitrate-induced plant-specific transcription factor subfamily impairs nitrate deficiency-triggered ROS accumulation and high-affinity nitrate transport. We isolated a quadruple mutant that displays 2.5-fold more high-affinity nitrate uptake activity. Abstract: Plants need to cope with strong variations of nitrogen availability in the soil. Although many molecular players are being discovered concerning how plants perceive NO3 − provision, it is less clear how plants recognize a lack of nitrogen. Following nitrogen removal, plants activate their nitrogen starvation response (NSR), which is characterized by the activation of very high-affinity nitrate transport systems (NRT2.4 and NRT2.5) and other sentinel genes involved in N remobilization such as GDH3 . Using a combination of functional genomics via transcription factor perturbation and molecular physiology studies, we show that the transcription factors belonging to the HHO subfamily are important regulators of NSR through two potential mechanisms. First, HHOs directly repress the high-affinity nitrate transporters, NRT2.4 and NRT2.5. hho mutants display increased high-affinity nitrate transport activity, opening up promising perspectives for biotechnological applications. Second, we show that reactive oxygen species (ROS) are important to control NSR in wild-type plants and that HRS1 and HHO1 overexpressors and mutants are affected in their ROS content, defining a potential feed-forward branch of the signaling pathway. Taken together, our results define the relationships of two types of molecular players controlling the NSR, namely ROS and the HHO transcription factors. This work (i) up opens perspectives on a poorly understood nutrient-related signaling pathway and (ii) defines targets for molecular breeding of plants with enhanced NO3 − uptake.